2019
DOI: 10.1111/pbr.12742
|View full text |Cite
|
Sign up to set email alerts
|

Development of colchicine‐induced tetraploid St. Augustinegrass (Stenotaphrum secundatum) lines

Abstract: St. Augustinegrass is well suited for lawns and commercial landscapes. While many genotypes are cross‐fertile, all cultivars are propagated vegetatively in sod production. To ensure varietal purity, development of sterile triploid hybrids by crossing tetraploid and diploid genotypes has been successfully used in other warm‐season turfgrasses. Applying this model in St. Augustinegrass would be beneficial to sod producers and turf managers who require purity for certification and uniformity for performance, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The PCA biplot further demonstrates the relationship between stolon internode length and SGR and between stolon diameter and leaf length (Figure 1b). After adding labels to the dataset indicating the ploidy levels of the germplasm [diploid (2 n = 18), triploid (2 n = 27), aneuploid (2 n = 28–32)] (Carbajal et al., 2019; Milla‐Lewis, Zuleta, Van Esbroeck, Quesenberry, & Kenworthy, 2013), the influence of ploidy on growth characteristics is clearly evident with increasing ploidy resulting in larger leaves and stolons (Figure 1b). This is consistent with other reports that higher ploidy is an important factor in increasing leaf and internode sizes in turfgrasses (Carbajal et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The PCA biplot further demonstrates the relationship between stolon internode length and SGR and between stolon diameter and leaf length (Figure 1b). After adding labels to the dataset indicating the ploidy levels of the germplasm [diploid (2 n = 18), triploid (2 n = 27), aneuploid (2 n = 28–32)] (Carbajal et al., 2019; Milla‐Lewis, Zuleta, Van Esbroeck, Quesenberry, & Kenworthy, 2013), the influence of ploidy on growth characteristics is clearly evident with increasing ploidy resulting in larger leaves and stolons (Figure 1b). This is consistent with other reports that higher ploidy is an important factor in increasing leaf and internode sizes in turfgrasses (Carbajal et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…(2013) previously reported that colchicine‐induced polypoid centipedegrass had increased stomatal size, and a similar effect was observed in St. Augustinegrass ( Stenotaphrum secundatum [Walt.] Kuntze) (Carbajal et al., 2019). The tetraploid line HW123 and the mixoploid line HW61 also had greater clipping yield than the other lines (with the exception of HW143), potentially indicating increased growth or leaf elongation rates for these lines.…”
Section: Discussionmentioning
confidence: 99%
“…Ploidy manipulation has been successfully used in many crop improvement programs, mainly to overcome species hybridization barriers, create sterile lines, facilitate interspecific gene transfer, and develop plant species with wider adaptability and desirable traits (Sattler et al., 2016; Singh et al., 1990; Tonosaki et al., 2018). Colchicine has been widely used to manipulate the ploidy of several plant species (Carbajal et al., 2019); however, herbicides trifluralin and oryzalin have been recently used for doubling chromosome numbers due to their lower toxicity, higher affinity to plant tubulins, and efficacy at lower concentrations (Touchell et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Since it is a low area and with clayey soils, in addition to clearance, some horizons of the soil were removed or homogenized and subsequently compacted. To raise the level, it was f illed with a mixture of sand, soil removed and remaining construction materials (Morales- Bautista et al, 2017) (this was considered as a reference sample of treated soil or TR3); although it is a fact that with these works the edaphological classif ication is lost, usually organic coverage is always implemented (Carbajal et al, 2019), that is why when the construction works f inished, San Agustín grass (Stenotaphrum secundatum) was rolled over the conservation area (Sastry et al, 2019). In each zone, directed sampling was performed with shovels and peaks, three geological strata were taken (problems) and another three samples were taken from a non-impacted surrounding area with similar edaphological characteristics (control).…”
Section: Study Areasmentioning
confidence: 99%